Social Media Attention Increases Article Visits: An Investigation on Article-Level Referral Data of PeerJ - Wang, Xianwen; Cui, Yunxue; Li, Qingchun; Guo, Xinhui (Frontiers in Research Metrics and Analytics, 2017)
In order to better understand the effect of social media in the dissemination of scholarly articles, employing the daily updated referral data of 110 PeerJ articles collected over a period of 345 days, we analyze the relationship between social media attention and article visitors directed by social media. Our results show that the social media presence of PeerJ articles is high. About 68.18% of the papers receive at least one tweet from Twitter accounts other than @PeerJ, the official account of the journal. Social media attention increases the dissemination of scholarly articles. Altmetrics could not only act as the complement of traditional citation measures, but also play an important role in increasing the article downloads and promoting the impacts of scholarly articles. There also exist significant correlation among the online attention from different social media platforms. Articles with more Facebook shares tend to get more tweets. The temporal trends show that social attention comes immediately following publication but does not last long, so do the social media directed article views.